2023
DOI: 10.1021/jacs.3c03486
|View full text |Cite
|
Sign up to set email alerts
|

Interfullerene Electronic Interactions and Excited-State Dynamics in Fullerene Dumbbell Conjugates

Abstract: Several dumbbell conjugates featuring M3N@I h -C80 (M = Sc, Y) and C60 were prepared to systematically investigate interfullerene electronic interactions and excited state dynamics. From electrochemical investigations, we concluded that the redox potentials of our M3N@I h -C80 (M = Sc, Y) dumbbells depend largely on the interfullerene electronic interactions. Assisted by DFT calculation, the unique role of metal atoms was highlighted. Most importantly, ultrafast spectroscopy experiments revealed symmetry-bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…[122][123][124][125] the insertion of different metals or metal clusters. 144,145 For instance, Lu 3 NCC 80 , a typical structure within the trimetallic nitride template (TNT) family, has a lower oxidation potential than C 60 and exhibits high stability compared to other EMFs. This property makes it an ideal electron donor, and in 2019, Martin and coworkers used Lu 3 NCC 80 in combination with C 60 as an acceptor to construct an ''all-fullerene'' donor-acceptor system.…”
Section: Fullerenes As Hostsmentioning
confidence: 99%
“…[122][123][124][125] the insertion of different metals or metal clusters. 144,145 For instance, Lu 3 NCC 80 , a typical structure within the trimetallic nitride template (TNT) family, has a lower oxidation potential than C 60 and exhibits high stability compared to other EMFs. This property makes it an ideal electron donor, and in 2019, Martin and coworkers used Lu 3 NCC 80 in combination with C 60 as an acceptor to construct an ''all-fullerene'' donor-acceptor system.…”
Section: Fullerenes As Hostsmentioning
confidence: 99%
“…Jablonski diagrams and photophysical dynamics of (e) C 60 -dumbbell, (f) Y 3 N@C 80 -dumbbell, and (g) Sc 3 N@C 80 -dumbbell. (a–g) Reproduced with permission from ref . Copyright 2023 American Chemical Society.…”
Section: Thermodynamically Stable Charge-separation Statementioning
confidence: 99%
“…Similarly, reducing the acceptors LUMO level also contributes to more stable CSs. Recently, we have designed a series of fullerene (C 60 ) and metallofullerene (Sc 3 N@C 80 , Y 3 N@C 80 ) dumbbell structures to systematically study the interfullerene electronic interactions and their impact on electron transfer . The research demonstrated that in C 60 dumbbell and Y 3 N@C 80 dumbbell molecules, large electrochemical gaps positioned CSs above the 1 LEs, thus preventing charge separation (Figure ).…”
Section: Thermodynamically Stable Charge-separation Statementioning
confidence: 99%
See 1 more Smart Citation
“…Since the seminal discovery in 1985 by Kroto, Smalley, Curl, and co-workers [ 1 ], fullerenes, specifically buckminsterfullerene C 60 , have intrigued the scientific community. The unique structure of fullerenes, characterized by a fully conjugated closed-cage structure, containing a mixture of hexagonal and pentagonal rings, have been recognized for the unique electronic [ 2 4 ], optical [ 5 6 ], and mechanical properties [ 7 8 ]. Despite the notable achievements in fullerene research and the potential applications in diverse fields, a significant obstacle remained for the use in biological studies: fullerenes are poorly soluble in polar solvents, including water and other water-miscible solvents [ 9 ].…”
Section: Introductionmentioning
confidence: 99%